Hoe, heaven, and hell : my boyhood in rural New Mexico - Garcia, Nasario (Albuquerque, New Mexico University of New Mexico, 2015)
Nasario Garcia grew up in Ojo del Padre, a village in the Rio Puerco Valley northwest of Albuquerque, the way rural New Mexicans had for generations. His parents built their own adobe house, raised their own food, hauled their water, and brought up their children to respect the old ways. When he was young, Garcia's mother taught him to mend his clothes and enlisted his aid in slaughtering chickens. Here he offers detailed accounts of these and other mundane tasks, explaining that doing laundry in tin tubs with a washboard represented progress for people accustomed to washing their clothes in the Rio Puerco and scrubbing them with stones. Life is an adventure, from hauling wood down from the mountains to getting a haircut to family dinners and celebration. Story after story, with details such as the P & G soap that his mother used, the menu at his uncle's wedding, the use of both Spanish and English when he started school, tell the story of a vanished way of life.
Forward by Marc Simmons; Acknowledgments; Introduction; My placita: setting the stage -- A broken window -- Respect, obedience, and morality -- The venerable kitchen -- Witchcraft, beliefs, and superstitions -- Dad: master kite builder -- Spring house cleaning -- Wash day meant pinto beans -- A fleet of flatirons -- Cleanliness: a sense of character -- Gold in lead barrels -- A trip to the Monte -- Wedding bells and the whole shebang -- May I sharpen my pencil? -- La Mantanza: a festive occasion -- A diaper, sliced potatoes, and vinegar -- It's posole time! -- From cleaning ditches to planting crops -- Sunbonnets, straw hats, and praying for rain -- Lent and Holy Week -- The three Cs: catechism, confusion, and communion -- Cattle roundups and camaraderie -- Fiestas, food, and fun -- Harvest time and field mice -- Canning time -- Polite Politicians -- Humor comes in a variety of ways -- Freedom: a priceless commodity -- From cradle to grave -- Hoe, heaven, and hell -- One final glimpse -- Bibliography: Books authored or edited by Nasario Garcia related to the Rio Puerco Valley
102598
Keywords: Garcia, Nasario -- Childhood and youth; New Mexico